Glossary building process based on specialed terminology and matalanguage from the video game "Super Robot Taisen OG : the moon dwellers". - Cevallos Peláez, Alejandro José (2017)
The research topic of this study is the Glossary building process based on specialized terminology and metalanguage from the video game “Super Robot Taisen OG: The Moon Dwellers”. The purpose is to describe the process of glossary building within the localization process of a video game. For the methodological approach we consider the following: for the philosophical framework we chose constructivism, for the approach we applied a qualitative one and for the method a case study was appropriate. We followed this research procedure: We identified the translatable assets within the video game using the research instruments available, then we proceeded to classify the translatable assets according to the function and purpose in the game, finally we used the appropriate strategies and techniques to render the terms in the target language. The most relevant conclusion we drew was that building a glossary for a video game requires translation strategies such as transcreation, loyalty or literal translation and translation techniques like generalization or adaptation.